Genetically modified human CD4+ T cells can be evaluated in vivo without lethal graft‐versus‐host disease. Issue 4 (18th July 2016) - Ali, Riyasat; Babad, Jeffrey; Follenzi, Antonia; Gebe, John A.; Brehm, Michael A.; Nepom, Gerald T.; Shultz, Leonard D.; Greiner, Dale L.; DiLorenzo, Teresa P.
Summary: Adoptive cell immunotherapy for human diseases, including the use of T cells modified to express an anti‐tumour T‐cell receptor (TCR) or chimeric antigen receptor, is showing promise as an effective treatment modality. Further advances would be accelerated by the availability of a mouse model that would permit human T‐cell engineering protocols and proposed genetic modifications to be evaluated in vivo . NOD‐ scid IL2rγ null (NSG) mice accept the engraftment of mature human T cells; however, long‐term evaluation of transferred cells has been hampered by the xenogeneic graft‐versus‐host disease (GVHD) that occurs soon after cell transfer. We modified human primary CD4 + T cells by lentiviral transduction to express a human TCR that recognizes a pancreatic beta cell‐derived peptide in the context of HLA‐DR4. The TCR‐transduced cells were transferred to NSG mice engineered to express HLA‐DR4 and to be deficient for murine class II MHC molecules. CD4 + T‐cell‐depleted peripheral blood mononuclear cells were also transferred to facilitate engraftment. The transduced cells exhibited long‐term survival (up to 3 months post‐transfer) and lethal GVHD was not observed. This favourable outcome was dependent upon the pre‐transfer T‐cell transduction and culture conditions, which influenced both the kinetics of engraftment and the development of GVHD. This approach should now permit human T‐cell transduction protocols and genetic modifications to be evaluated in vivo, and it should also facilitate the development of human disease models that incorporate human T cells.